Compromised word-level neural tracking in the high-gamma band for children with attention deficit hyperactivity disorder - Luo, Cheng; Gao, Yayue; Fan, Jianing; Liu, Yang; Yu, Yonglin; Zhang, Xin (Frontiers in Human Neuroscience, 2023)
Children with attention deficit hyperactivity disorder (ADHD) exhibit pervasive difficulties in speech perception. Given that speech recognition involves both acoustic and linguistic processing stages, it remains unclear which stage of speech processing is impaired in children with ADHD. To investigate this issue, we measured neural tracking of speech at syllable and word levels using electroencephalography (EEG), and evaluated the relationship between neural responses and ADHD symptoms in 6-8 years old children. Twenty-three children participated in the current experiment, and their ADHD symptoms were assessed with SNAP-IV questionnaires. When the children listened to speech, reliable neural tracking of syllables and words was observed in both the low-frequency band and the high-gamma band. Nevertheless, the neural tracking of words in the high-gamma band showed an anti-correlation with the ADHD symptom scores of the children. These results indicate that ADHD prominently impairs cortical encoding of linguistic information (e.g., words) in speech perception.